Effective Program Management in Arabic Intensive Courses: A Case Study - Lubis, Amanda; Mufidah, Nuril; Karim Amrullah, Abu Malik (Universitas Islam Negeri Raden Intan Lampung, 2024)
Program management includes planning, staffing, organizing, directing, coordinating, and budgeting. The focus of this research is to describe the planning, organization and staffing at arabic intensive course. This study used descriptive qualitative method. Data collection techniques include observation, interviews with tutors, and documentation. The subject of this research is the Al-Azhar arabic intensive course Pare in 2023. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of this research: 1) Program planning management uses modern methods to provide convenience to course participants who are constrained by distance by using online and traditional platforms, which means direct/face-to-face meetings. 2) The management of organizing the program uses a top down method, namely the manager gives direct verbal orders to members. 3) Staff placement with the presupervisory program type means that position filling is carried out by section leaders to select, determine and place staff according to needs